142k views
11 votes
Solve for x: 3(x - 1) - 5x = 1 - 7(2 + x)
ASAP PLS

User Tahamv
by
4.8k points

2 Answers

14 votes

3(x - 1) - 5x = 1 - 7(2 + x)

3x - 3 - 5x = 1 - 14 + 7x

3x - 5x = -2x

-2x - 3 = 1 - 14 + 7x

1 - 14 = -13

-2x - 3 = -13 + 7x

+3 | +3 + 7x

-2x | -10 + 7x

2 | 2

x = -10 + 4.5x

4.5 rounded is 5.

x = -10 + 5x

-10/5 = -2

x = -2

Let me know if this is the correct answer. :)

User Elbbard
by
4.6k points
8 votes

Answer:

x = -2

Explanation:

hdiwnohdiwmnwidn

Solve for x: 3(x - 1) - 5x = 1 - 7(2 + x) ASAP PLS-example-1
User Paulusm
by
4.1k points